P221 The effect of a heat and moisture exchange mask to reduce exercise induced cough and bronchoconstriction. (12th November 2019) - Jackson, A; Hull, J; Hopkins, J; Fletcher, H; Birring, S; Dickinson, J
Abstract : The present study aimed to determine if a heat and moisture exchanger (HME) face mask is effective in protecting against acute bronchoconstriction and post exercise cough in response to a cycle challenge in a cold, dry environment in asthmatic individuals. Twenty-six participants with a clinician diagnosis of asthma (20 males, 6 females, age: 27.6±9.2 yrs, &Vdot;O2 peak: 42.75±8.17 ml.kg.min -1 ) completed three standardised exercise challenges (EX) on a cycle ergometer at 8 o C and 24% RH in a randomised order. Participants wore either an HME mask (MASK), a sham mask (SHAM), or no mask (CON). Following a 3-min set warm up participants completed 6-min cycling at 80% peak power output. Before and after EX, maximal flow volume loops were recorded. Immediately post EX participants were fitted with a Leicester Cough Monitor (LCM) which they wore for 24-hours. Results were analysed using repeated measures ANOVA and Friedman's tests and data presented as the mean±SD or median score. Eleven participants failed to demonstrate evidence of EIB and were removed from the analysis. There was a difference in the% fall in FEV1 following EX (MASK: -6.0, SHAM: -11.0, CON: -13.0%, P<0.01), with the% fall following CON greater than that of MASK (p<0.01). No differences were found between EX in cough count per hour over the 24-hour monitoring period or the number of coughs in the first hour post EX. HME masks can attenuate bronchoconstriction but not cough in asthmatic individuals when exercising in cold, dry environments.